Bimbingan Teknis Pembuatan Pupuk Organik Tandan Kosong Kelapa Sawit (TKKS) di Kabupaten Kolaka - La Mpia; Juniaty Aruan Bulawan; La Ode Muhsafaat; Hasbiadi Hasbiadi (Yayasan Literasi Sains Indonesia, 2022)
Oil palm empty fruit bunches are the main waste from the palm oil processing industry and are a source of organic matter rich in nutrients N, P, K, and Mg. Composting empty palm fruit bunches naturally takes quite a long time. Techniques to speed up the process of decomposition of organic matter is done by giving activators. Activators are microbial decomposers that act as catalysts to speed up the composting process and make the composting products perfect with good quality. The potential for empty oil palm bunches in Tanggetada District, especially Petudua Village, is very abundant. The people in Petudua Village do not yet know the benefits of empty palm fruit bunches, so they are left lying around which can disturb the surrounding environment. This technical assistance aims to guide the people of Petudua Village on the steps for making organic fertilizer sourced from empty oil palm fruit bunches. The stages of this activity include lectures, training and discussions. The result of this technical assistance is the knowledge of the people of Petudua Village about the steps for making and the procedure for making organic fertilizer from empty oil palm bunches.